PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN KUALITAS HASIL BELAJAR SISWA KELAS I PADA PEMBELAJARAN MATEMATIKA MATERI OPERASI HITUNG DI SDN KEPATIHAN 05 JEMBER - fatmawati, wiwik (Kadikma, 2019)
This research aims to determine how to improve the quality of student learning outcomes in mathematics grade 1 arithmetic operating materials by applying the techniques of mind mapping in SDN Kepatihan 05 Jember. This research is a classroom action research with the Hopkins cycle design. The research approach used is a qualitative descriptive approach. The subjects were 30 students of grade 1 SDN 5 Kepatihan Jember. This research consists of four stages: planning, implementing actions, observing and reflecting. Data collection techniques used in this study are observation, tests, field notes and documentation. The results obtained are student learning outcomes 71.85 in the first cycle increased to 95.55 in the third cycle during the study. The conclusion of this study is the application of the Mind Mapping learning method can significantly improve the quality of learning outcomes in the count operations material each cycle.